1994
DOI: 10.1128/jb.176.3.932-934.1994
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a hydride-Meisenheimer complex as a metabolite of 2,4,6-trinitrotoluene by a Mycobacterium strain

Abstract: A bacterial strain, Mycobacterium sp. strain HL 4-NT-1, enriched with 4-nitrotoluene as its sole source of nitrogen, was able to metabolize 2,4,6-trinitrotoluene under aerobic conditions. The dark red-brown metabolite, which accumulated in the culture fluid, was identified as a hydride-Meisenheimer complex by comparison with an authentic synthetic sample.In the course of large-scale manufacturing and handling of explosives, both soil and groundwater were contaminated extensively with polynitroaromatic compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(107 citation statements)
references
References 12 publications
7
99
1
Order By: Relevance
“…These resist further oxidative microbial degradation and form a very serious problem due to their higher solubility, toxicity and genotoxicity as compared to TNT (see chapter 1. Another reductive degradation mechanism by aerobic organisms has been described: the nucleophilic attack by a hydride ion to form a hydride-Meisenheimer complex, which may be followed by the release of nitrite (Vorbeck et al 1994). Duque et al (1993) reported the isolation and characterisation of Pseudomonas sp.…”
Section: Phanerochaete Chrysosporiummentioning
confidence: 99%
See 1 more Smart Citation
“…These resist further oxidative microbial degradation and form a very serious problem due to their higher solubility, toxicity and genotoxicity as compared to TNT (see chapter 1. Another reductive degradation mechanism by aerobic organisms has been described: the nucleophilic attack by a hydride ion to form a hydride-Meisenheimer complex, which may be followed by the release of nitrite (Vorbeck et al 1994). Duque et al (1993) reported the isolation and characterisation of Pseudomonas sp.…”
Section: Phanerochaete Chrysosporiummentioning
confidence: 99%
“…clone A. The presence of an FF-TNT complex was successfully demonstrated when Rhodococcus erythropolis HL PM-1 or Mycobacterium strain HL 4-NT-1 were exposed to TNT (Vorbeck et al 1994). Unlike the H--picric acid complex, the corresponding TNT complex undergoes neither nitrite elimination nor re-aromatisation to 2,4-DNT or 2,6-DNT.…”
Section: Phanerochaete Chrysosporiummentioning
confidence: 99%
“…Also, aerobic pathways result in formation of azoxy polymers formed through condensation of nitroso intermediates under aerobic conditions. Vorbeck et al (1994) also isolated a transient hydride-Meisenheimer complex product from TNT degradation under aerobic conditions. The other major aerobic degradative mechanism involves direct removal of the nitro group as nitrite (Spain et al, 1979;Zeyer and Kearney, 1984;Bruhn et al, 1987).…”
Section: Mechanisms and Productsmentioning
confidence: 99%
“…Of particular interest to our current work is the presence of a hydride transfer channel with 1,3,5-triazine to form a hydride-Meisenheimer complex. Recently, these complexes have been identified in the biodegradation of nitroaromatics [30][31][32][33][34]. Although fragmentation patterns of the hydrideMeisenheimer complex of trinitrotoluene, [TNT + H] σ-adducts [35].…”
Section: Introductionmentioning
confidence: 99%